2016
DOI: 10.1155/2016/6413713
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Adverse Infant Outcomes Associated with Maternal Tuberculosis in a Low Burden Setting: A Population-Based Retrospective Cohort Study

Abstract: Background. Maternal tuberculosis (TB) may be associated with increased risk of adverse infant outcomes. Study Design. We examined the risk of low birth weight (LBW), small for gestational age (SGA), and preterm birth (<37 weeks) associated with maternal TB in a retrospective population-based Washington State cohort using linked infant birth certificate and maternal delivery hospitalization discharge records. We identified 134 women with births between 1987 and 2012 with TB-associated ICD-9 diagnosis codes at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
2
2
0
3
Order By: Relevance
“…It has also been suggested that pregnancy may confer an increased risk of LTBI reactivation [ 5 , 6 ]. Furthermore, since active TB is associated with adverse pregnancy outcomes [ 7 9 ], TB screening is recommended during antenatal care.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that pregnancy may confer an increased risk of LTBI reactivation [ 5 , 6 ]. Furthermore, since active TB is associated with adverse pregnancy outcomes [ 7 9 ], TB screening is recommended during antenatal care.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the possibility of postnatal transmission may exist when the infant’s mother wasn’t isolated immediately with the infant after delivery. According to Sylvia [ 11 ] et al population-based retrospective cohort study, infants born to mothers with maternal TB had similar chance of preterm delivery compared to those born to mothers without TB. After adjusting women’s conditions to the same, the chance of preterm delivery was decreased but remained similar between infants born to mothers with and without TB, indicating that there is no association with prematurity.…”
Section: Discussionmentioning
confidence: 99%
“…Schwangere haben ein erhöhtes Risiko, an Tuberkulose zu erkranken, insbesondere, wenn eine HIV-Koinfektion besteht. Kinder von Frauen, die während der Schwangerschaft an Tuberkulose erkranken, zeigen häufiger ein niedrigeres Geburtsgewicht und sind häufiger zu klein bezogen auf das Gestationsalter im Vergleich zu Kindern von gesunden Müttern [1][2][3].…”
Section: Hintergrundunclassified
“…Epidemiologische Daten aus den USA zeigen, dass die TB-Inzidenz in den ersten 180 Tagen post partum auch in TB-Niedriginzidenzländern erhöht ist, möglicherweise auch bereits schon während der Schwangerschaft [2].…”
Section: Hintergrundunclassified